The long 1968 : revisions and new perspectives - Sherman, Daniel J.; Dijk, Ruud van; Alinder, Jasmine, 1969-; Aneesh, A. (Aneesh), 1964- (21st Century studies, 2013)
From the mid-1960s to the early 1970s, revolutions in theory, politics, and cultural experimentation swept around the world. These changes had as great a transformative impact on the right as on the left. A touchstone for activists, artists, and theorists of all stripes, the year 1968 has taken on new significance. This book explores the wide-ranging impact of the year and its aftermath in politics, theory, the arts, and international relations - and its uses in the twenty-first century.--description provided by publisher.